2010
DOI: 10.1007/s12011-010-8612-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Dietary vitamin E or C Decrease Egg Yolk Cholesterol?

Abstract: An experiment was conducted to determine the effect of dietary vitamin E and C on serum metabolites, yolk cholesterol, egg quality, and performance of layer hens. One hundred sixty-eight commercial Hy-Line W-36 layer hens were randomly divided into seven groups and six replicates with four hens in each. Dietary treatments were introduced after the pre-experimental period (10 days) to adjust egg production. Treatments were levels of vitamin E or C (100, 200, and 400 mg/kg diet) supplementation to the basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Similar to results obtained in the present study, Sahin et al [17] reported that supplemental vitamin E in Japanese quail decreased cholesterol concentrations of egg yolk. Mohiti-Asli and Zaghari [18] reported that egg yolk cholesterol concentrations decreased linearly by antioxidant vitamin supplementation in commercial layer hens, and vitamin E was more effective than vitamin C. The literature provides strong evidence that vitamin E intake much higher than the current recommendations can contribute to or improve human and layer hen health [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to results obtained in the present study, Sahin et al [17] reported that supplemental vitamin E in Japanese quail decreased cholesterol concentrations of egg yolk. Mohiti-Asli and Zaghari [18] reported that egg yolk cholesterol concentrations decreased linearly by antioxidant vitamin supplementation in commercial layer hens, and vitamin E was more effective than vitamin C. The literature provides strong evidence that vitamin E intake much higher than the current recommendations can contribute to or improve human and layer hen health [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%